The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4025/actasciagron.v36i4.18057
|View full text |Cite
|
Sign up to set email alerts
|

<b>Germination and biochemical changes in ‘Formosa’ papaya seeds treated with plant hormones

Abstract: ABSTRACT. This study aimed to investigate the effects of growth regulators on germination rates and biochemical compound concentrations in Carica papaya L. seeds ('Formosa' group). The seeds were harvested from fruits at maturation stages 3 and 5 (50 and 75% yellow fruit skin, respectively). The effects of 2-chloroethylphosphonic acid (CEPA), KNO 3 and gibberellic acid (GA 3 ) on seed germination, germination index speed, soluble sugars, starch, lipids, soluble proteins and total proteins of the papaya seeds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The application of a combined hormone regulator brings cross‐responses between dormancy and germination when there is a modification of gibberellin/abscisic acid relationships. The use of gibberellic acid (gibberellin) increases germination by reducing the concentrations of abscisic acid, the main promoter of seed dormancy (Zanotti, Dias, Barros, DaMatta, & Oliveira, ). Abscisic acid regulates the mobilization of storage lipids in the endosperm.…”
Section: Discussionmentioning
confidence: 99%
“…The application of a combined hormone regulator brings cross‐responses between dormancy and germination when there is a modification of gibberellin/abscisic acid relationships. The use of gibberellic acid (gibberellin) increases germination by reducing the concentrations of abscisic acid, the main promoter of seed dormancy (Zanotti, Dias, Barros, DaMatta, & Oliveira, ). Abscisic acid regulates the mobilization of storage lipids in the endosperm.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinins promoted seed germination in the present study which could be, as for GA, through modulation of protein synthesis (26,37,38). This group of growth-promoting PGRs has been indicated in regulating seed germination and is active in all stages (16,39).…”
Section: Discussionmentioning
confidence: 50%
“…This effect has been verified in several plant species. Zanotti et al (2014) observed that gibberellin was responsible for promoting greater mobilization of lipids in papaya seeds, and it can also be the substrate for producing energy for the germination process in the gluconeogenesis process, according to Heldt and Piechulla (2011). In their evaluations, the use of gibberellin in seed treatment was effective in promoting almost double the germination in relation to the control treatment.…”
Section: Discussionmentioning
confidence: 99%